Characterization of Bioactive Components in Edible Algae - Pereira, Leonel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Algae have been used since ancient times as food for humans, animal feed, agricultural fertilizer, and as a source of substances for therapeutic use. Currently, seaweed represents a vast source of raw materials used in the pharmaceutical, food, traditional medicine, and cosmetics industries. They are nutritionally valuable, both fresh and dried, or as ingredients in a wide variety of pre-made foods. In particular, seaweed contains significant amounts of protein, lipids, minerals, and vitamins. Information is limited on the role of algae and their metabolites in therapy. Only a few taxa have been studied for use in medicine. Many traditional cultures report the healing powers of selected algae in tropical and subtropical marine forms. This is especially true in the maritime areas of Asia, where the sea plays a significant role in daily activities. However, currently, only a few genera and species of algae are involved in aspects of medicine and therapy. The beneficial uses of seaweed or seaweed products include those that can mimic specific manifestations of human disease, production of antibiotic compounds, or improved human nutrition.